1991
DOI: 10.3406/arsci.1991.1263
|View full text |Cite
|
Sign up to set email alerts
|

Quelques observations complémentaires sur les altérations de composition des céramiques au cours du temps : cas de quelques alcalins et alcalino-terreux

Abstract: On rappelle que les céramiques calcaires fortement surcuites sont particulièrement sensibles aux phénomènes de lessivage. Ceux-ci se traduisent par l'élimination d'une fraction très importante du potassium, mais également du baryum. La présence d'une phase vitreuse, instable, riche en potassium (et en baryum) est sans doute à l'origine de cette sensibilité Ces fixations se produisent également dans le cas des céramiques calcaires non surcuites. On en donne deux exemples pou Sr et Ba, dans un contexte fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 2 publications
1
24
0
3
Order By: Relevance
“…In 1976, Picon examined two sherds of calcareous pottery at several spots with a varying degree of overfiring and observed a leaching of K, especially at the spots that show signs of a medium overfiring. Later, Picon (1991) found an enrichment in the Na, Mg and Sr concentrations at the same spots and proposed the crystallization of zeolites as an explanation for this phenomenon. In the years that followed, several comparative studies (e.g., Buxeda and Gurt 1998; Buxeda 1999 and references therein; Buxeda et al 2001a, 2002) detected analcime in various sample sets in relation to a leaching of K, and showed that the intensity of analcime reflexes in X‐ray diffractograms increases with the equivalent firing temperatures of the analysed sherds.…”
Section: Introductionmentioning
confidence: 91%
“…In 1976, Picon examined two sherds of calcareous pottery at several spots with a varying degree of overfiring and observed a leaching of K, especially at the spots that show signs of a medium overfiring. Later, Picon (1991) found an enrichment in the Na, Mg and Sr concentrations at the same spots and proposed the crystallization of zeolites as an explanation for this phenomenon. In the years that followed, several comparative studies (e.g., Buxeda and Gurt 1998; Buxeda 1999 and references therein; Buxeda et al 2001a, 2002) detected analcime in various sample sets in relation to a leaching of K, and showed that the intensity of analcime reflexes in X‐ray diffractograms increases with the equivalent firing temperatures of the analysed sherds.…”
Section: Introductionmentioning
confidence: 91%
“…Burial load, temperature variations and frost can contribute to alteration, but the most effective processes are generally due to circulating water, which may soak archaeological objects, dissolving, weathering or precipitating secondary mineral phases. Significant bulk chemical (Lemoine et al 1981; Picon 1985; Walter and Besnus 1989; Picon 1991) and mineralogical modifications (Heimann and Maggetti 1981) are commonly observed and reported in archaeometric studies on pottery. In many cases, as considerable deviations from the original mineralogical and chemical composition may make the use of analytical data for provenance and technological studies misleading (Buxeda i Garrigós et al 2001), these processes must be ascertained by petrographic, geochemical and mineralogical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Abella, the data support such an interpretation (vid., Buxeda & Cau, 1995a). In relation with the values ln(Ba/SiO 2 ) and ln(Sr/SiO 2 ), contaminations of Ba and Sr have also been reported (for example, Bieber, 1977;Olin et al, 1978;Freestone et al, 1985;Picon, 1985b;Picon, 1987;Schmitt, 1989;Béarat, 1990;Picon, 1991). In the case of Abella, the data suggest the existence of a certain association between the contamination of calcium, barium and strontium, especially affecting those individuals in mineralogical categories C1 and C2, that are buried in the deposition contexts E/Q2.…”
Section: The Interpretation Of the Existing Structurementioning
confidence: 99%
“…In this fabric we can observe the effect of two different, possibly partially related, processes that cause the contamination of sodium and the lixiviation of potassium, perhaps because of the alteration of the glassy phase (for example, Picon, 1976;Segebade & Lutz, 1980;Lemoine et al, 1981;Schmitt, 1989;Picon, 1991). This lixiviation is not observed in all the individuals in category C4, but, what has to be taken into consideration is that all the individuals in this category present, with different intensities, peaks of leucite, a potash feldspatoid ( Figure 5 and Figure 6).…”
Section: The Interpretation Of the Existing Structurementioning
confidence: 99%
See 1 more Smart Citation